Centering ability and dentin removal of rotary systems in curved root canals - Moradi, Saeed; Talati, Ali; Monajem Zadeh, Ali (Iranian Endodontic Journal, 2009)
INTRODUCTION: The aim of this study was to compare centering ability and dentin removal of three rotary systems in curved root canals of extracted teeth. MATERIALS AND METHODS: Sixty root canals of mandibular first molars with curvatures ranging between 25-35o were divided into three groups of 20 teeth each. Based on pre-instrumentation radiographs that assessed the angle and the radius of canal curvatures, teeth with curvatures were equally spread between the three groups. The root canals were sectioned horizontally at two levels before preparation and then remounted onto the muffle. All root canals were prepared using a low-torque control motor with Mtwo or Medin or Race instruments. Cross sectional images were obtained before and after instrumentation. Cross-sectional area and centering ability were evaluated. The data were analyzed using the one-way ANOVA and Tukey tests. RESULTS: Neither instrument fracture nor permanent deformation occurred during preparations. The best centering ability was obtained by Mtwo instruments compare to Race and Medin instruments. In the coronal and middle sections, Mtwo removed less dentin than Race and Medin; while the difference in the apical section was not significant. CONCLUSION: Under the conditions of this study, the debridement of root canals was more conservative with Mtwo. The canals prepared with these instruments were better centered in all three regions of the root.